Being moved is a positive emotion, and emotions should not be equated with their vernacular labels. (29th November 2017) - Schubert, Thomas W.; Seibt, Beate; Zickfeld, Janis H.; Blomster, Johanna K.; Fiske, Alan P.
Abstract: As evidence for the second process of the Embracing factor, the target article characterizes being moved as a mixed emotion linked to sadness through metonymy. We question these characterizations and argue that emotions should not be equated with their vernacular labels.